Investigating the effects of TREM2, APOE and PILRα variants on microglial functions and neuronal loss - Popescu, Sandra Alma (Apollo - University of Cambridge Repository, 2023)
Microglia are the primary immune cells of the central nervous system (CNS). They utilise a host of signals, receptors, and processes to maintain homeostasis and to resolve exogenous and endogenous insults in the brain. Mounting evidence over recent years has highlighted the central role of microglia in neurodegenerative diseases, including Alzheimer’s disease (AD). However, whether microglia are beneficial in AD, detrimental or both, is an active area of research. Genome wide association studies (GWAS) have identified several AD-associated genes, many of which are expressed by microglia. Delineating the role of these genes and their proteins could help to further our understanding of AD pathogenesis and to uncover novel therapeutic targets. In this dissertation, I present findings on the roles of AD-risk associated variants of TREM2, APOE and PILRα in microglial functions and neuronal loss. Triggering receptor on myeloid cells 2 (TREM2) is an innate immune receptor, primarily expressed by microglia in the CNS and upregulated on the surface of microglia associated with amyloid plaques in AD. Individuals heterozygous for the R47H variant of TREM2 have greatly increased risk of developing late onset Alzheimer’s disease (LOAD). I examined the effects of TREM2 knock-out (KO), and expression of wild-type (WT) and R47H human TREM2 in the murine microglial cell line, BV-2. Expression of R47H TREM2 increased BV-2 phagocytosis of isolated synapses (synaptosomes) with exposed phosphatidylserine, and increased uptake of phosphatidylserine-beads. Phosphatidylserine is a ligand of TREM2 and an "eat-me" signal exposed on the surface of apoptotic cells and stressed-but- viable neurons. Addition of BV-2 microglia, expressing R47H TREM2 or with TREM2 KO, to primary mouse neuronal-glial cultures caused neuronal loss, not observed with addition of BV-2 microglia expressing WT TREM2. This neuronal loss was prevented by using annexin V to block exposed phosphatidylserine suggesting that this loss might be mediated by microglial phagocytosis of neurons exposing phosphatidylserine. These findings suggest a mechanism by which R47H TREM2 may increase AD risk, by increasing microglial phagocytosis of synapses and neurons exposing phosphatidylserine. It also indicates that the R47H mutation in TREM2 may cause a toxic gain-of-function and suggests that the common variant of TREM2 may also mediate microglial phagocytosis of synapses and neurons during AD, only less so than the R47H variant. If this is the case, then the therapeutic implications are that TREM2 should be inhibited in AD patients as opposed to the current therapeutic focus which is on activating TREM2 with antibodies. These findings on TREM2 were recently published in Popescu et al. (2023) in the journal GLIA. A soluble form of TREM2 (sTREM2) is found in humans and is produced in two ways, either by proteolytic cleavage of the ectodomain from full-length TREM2 or through alternative splicing. There is evidence that sTREM2 may have beneficial roles in AD and it is being investigated as a possible biomarker for neurodegenerative disease. I found that treatment of primary neuronal-glial cultures with WT sTREM2 appeared to reduce neuronal loss induced by co-culture with TREM2 KO BV-2 microglia. This neuroprotection was not observed with addition of R47H sTREM2, suggesting that this could be a further contributing factor to the neuroprotection observed with addition of WT TREM2 BV-2 to neuronal-glial cultures compared with addition of R47H TREM2 or TREM2 KO BV-2 microglia. Apolipoprotein E (APOE) is a secreted protein involved in lipid transport. There exist three common isoforms in humans, APOE2, APOE3 and APOE4. APOE4 is the strongest genetic risk factor associated with LOAD while APOE2 is associated with a reduced risk of LOAD. I found that addition of human APOE2 protein to primary rat neuronal-glial cultures reduced lipopolysaccharide (LPS)-induced neuronal loss, and that this neuroprotection was not observed with addition of APOE3 or APOE4. I also found that APOE2, and not APOE3 or APOE4, reduced LPS-induced microglial proliferation in the neuronal-glial cultures where the neuroprotection was observed. This suggests that APOE2 might be neuroprotective by reducing microglial proliferation. While further work is required to understand the underlying mechanisms, it is possible that this neuroprotective effect by APOE2 could be a contributing factor in the associated reduced risk of AD. This also highlights the possibility of APOE2 protein being developed into a neuroprotective treatment. Additionally, I found that incubation of phosphatidylserine-exposing synaptosomes with APOE2/E4 reduced their phagocytic uptake by primary microglia to a similar level as treatment with annexin V, and this was not found when treating microglia directly with APOE2/E4. This suggests that APOE may act as a ‘nopsonin’, i.e. an extracellular protein that inhibits phagocytosis when bound to a potential phagocytic target, possibly via blocking phosphatidylserine. If this is the case, then APOE may prevent phagocytosis of phosphatidylserine-exposing targets including synapses, neurons, and debris. Paired immunoglobulin-like type 2 receptor alpha (PILRα) is an inhibitory immune receptor expressed on the surface of microglia. Recent genome studies have linked the R78 PILRα variant to reduced risk of AD. There is currently little published research on this protective effect, especially relating to microglia. I examined the effects of wild type G78 and variant R78 human PILRα expression in the human microglial cell line CHME-3. Expression of G78 and R78 PILRα increased CHME- 3 release of the pro-inflammatory cytokine IL-6 and expression of R78 PILRα reduced microglial proliferation. However, PILRα expression had no significant effect on microglial phagocytosis of phosphatidylserine beads or neuronal debris and had no effect on LPS-induced release of IL-6. My findings on PILRα only scratch the surface and further work is required to elucidate the role of PILRα and its R78 variant in microglia. Together, these data expand our understanding of how TREM2, APOE and PILRα may be involved in AD-risk and support the idea that these proteins are relevant therapeutic targets for AD.
Keywords: Alzheimer's Disease; Neurodegeneration; Microglia; TREM2; APOE; PILRA; Neuronal Loss